Does obesity hinder radiotherapy in endometrial cancer patients? The implementation of new techniques in adjuvant radiotherapy – focus on obese patients - Moszyńska-Zielińska, Małgorzata; Chałubińska-Fendler, Justyna; Gottwald, Leszek; Żytko, Leszek; Bigos, Ewelina; Fijuth, Jacek (Menopause Review/Przegląd Menopauzalny, 2014)
The increasing incidence of obesity in Poland and its relation to endometrioid endometrial cancer (EEC) is resulting in the increasing necessity of treating obese women. Treatment of an overweight patient with EEC may impede not only the surgical procedures but also radiotherapy, especially external beam radiotherapy (EBRT). The problems arise both during treatment planning and when delivering each fraction due to the difficulty of positioning such a patient – it implies the danger of underdosing targets and overdosing organs at risk. Willingness to use dynamic techniques in radiation oncology has increased for patients with EEC, even those who are obese. During EBRT careful daily verification is necessary for both safety and treatment accuracy. The most accurate method of verification is cone beam computed tomography (CBCT) with soft tissue assessment, although it is time consuming and often requires a radiation oncologist. In order to improve the quality of such treatment, the authors present the practical aspects of planning and treatment itself by means of dynamic techniques in EBRT. The authors indicate the advantages and disadvantages of different types of on-board imaging (OBI) verification images. Considering the scanty amount of literature in this field, it is necessary to conduct further research in order to highlight proper planning and treatment of obese endometrial cancer patients. The review of the literature shows that all centres that wish to use EBRT for gynaecological tumours should develop their own protocols on qualification, planning the treatment and methods of verifying the patients’ positioning.